2019
DOI: 10.1021/acs.joc.9b01133
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and RNA-Binding Properties of Extended Nucleobases for Triplex-Forming Peptide Nucleic Acids

Abstract: Triple-helix formation, using Hoogsteen hydrogen bonding of triplex-forming oligonucleotides, represents an attractive method for sequence-specific recognition of double-stranded nucleic acids. However, practical applications using triple-helix-forming oligonucleotides and their analogues are limited to long homopurine sequences. The key problem for recognition of pyrimidines is that they present only one hydrogen-bond acceptor or donor group in the major groove. Herein, we report our first attempt to overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…Presumably, this twist resulted from repulsions of the carbonyl with the O4 on the Io pyrimidine ring and repulsions of the benzamide NH 2 with the ortho ‐hydrogen (C‐6) on the benzamide ring. Nonetheless, compared to previously modelled extended nucleobases, [13] this scaffold represented the most planar base triple observed to date.…”
Section: Figurementioning
confidence: 84%
See 2 more Smart Citations
“…Presumably, this twist resulted from repulsions of the carbonyl with the O4 on the Io pyrimidine ring and repulsions of the benzamide NH 2 with the ortho ‐hydrogen (C‐6) on the benzamide ring. Nonetheless, compared to previously modelled extended nucleobases, [13] this scaffold represented the most planar base triple observed to date.…”
Section: Figurementioning
confidence: 84%
“…We reported an extended triazole‐containing nucleobase that showed moderate binding with a single modification, but the simple triazolyl‐substituted pyrimidine showed improved binding, similar to T control (Figure 2 c). [13] Finally, Hudson and Wojciechowski reported that the PNA 2 :RNA triplex between Ac‐TTTTTTK‐NH 2 and poly(riboadenylic acid) was stabilized, as observed by UV melting, when a single isoorotamide modification was introduced into the middle of the poly T PNA oligomer (Figure 2 d). [14] Though this phenomenon was proposed to be due to both increased base‐stacking interactions and the cationic ammonium moiety, it was not explored further.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…This study was the first demonstration of the biological effect of binding of M-and P-modified PNAs to dsRNA in live cells. Recent work from our labs [120] systematically surveyed simple nitrogen heterocycles and found that the 3-pyridazinyl nucleobase formed significantly more stable triplets with C-G than other heterocycles, including P. Several groups have explored extended PNA nucleobases for recognition of C-G base pairs [121,122]. Chen and co-workers followed up on original work by Seidman [123] and showed that Q (Figure 7) in PNAs targeting dsRNA, recognized C-G base pairs with good selectivity.…”
Section: Pna Nucleobases For Hoogsteen Recognition Of Pyrimidinesmentioning
confidence: 99%
“…[96] However, TFO based technologies have shown practical issues in terms of limitations of use to only homo-purine sequences. They were not able to recognize pyrimidines as they possess only one-hydrogen acceptor in major DNA groove [97]. Further innovations to overcome this issue resulted in development of Peptide Nucleic Acids (PNAs) supplanted by nucleobases which could overcome this problem and were able to address this issue [97].…”
Section: Table-2: Generalized Comparison Between Various Delivery Modes For Crispr Gene Machinerymentioning
confidence: 99%